Antimicrobial-Induced Cytopenia and Bone Marrow Hypocellularity in Patients with Cirrhosis - Patil, Anupama (Bone Marrow Res, 2018)
There is great variation in cytopenias in cirrhotic patients with same severity and hypersplenism and their causative factors are not clear. Recent studies have highlighted the role of gut microbiome in regulation of constant and emergency hematopoiesis. Broad-spectrum antibiotics can disrupt the homeostatic or adaptive microbiota in cirrhosis, leading to impaired hematopoiesis and a higher susceptibility to infections. We studied all patients with cirrhosis with cytopenia (anemia, leucopenia, and/or thrombocytopenia), admitted in the Institute of Liver & Biliary Sciences, between January 2016 and July 2017, who underwent a bone marrow examination. The effect of the different antimicrobial agents on peripheral blood counts and bone marrow cellularity was assessed. A total of 196 patients' data was analyzed for this study. Patients on antimicrobials (n = 115) had significantly lower hemoglobin (p < 0.001), total leucocyte count (p = 0.048), and platelet count (p = 0.043) compared to patients not on antimicrobials. On unadjusted analysis, significant association with thrombocytopenia existed in beta-lactams (OR = 1.56, 95% CI = 1.06–2.40), quinolones (OR = 1.66, 95% CI = 1.11–2.61), and antifungals (OR = 2.24, 95% CI = 1.96–4.34). Cephalosporins were found to be significantly associated with anemia (OR = 1.91, 95% CI = 1.07–3.41). Patients who received antimicrobials had hypocellular marrow (p < 0.001) as compared to nonrecipients of antibiotics. The adjusted analysis showed that quinolones and beta-lactam antibiotics are the drug classes having significant association with thrombocytopenia and alternative class of drug should be explored in these patients to avoid severe thrombocytopenia.